Partisipasi Bidan Dalam Implementasi Program Triple Eliminasi HIV, Sifilis dan Hepatitis B dari Ibu ke Anak di Pulau Lombok - Siti Mardiyah WD; Catur Esty Pamungkas (Universitas Sari Mulia, 2021)
Latar Belakang:Jumlah infeksi HIV yang Provinsi NTB dari pertama kali ditemukan sampai dengan dengan maret 2017 sebanyak 1.279, sedangkan jumlah infeksi AIDS dari tahun 1987 sampai dengan Maret 2017 sebanyak 704 orang. Faktor resiko penularan terbanyak melalui heteroseksual (68%), penasun (11%), diikuti homoseksual (4%) dan penularan melalui perinatal (3%) (Ditjen P2P Kemenkes RI, 2017). Prevalensi pada ibu hamil untuk HIV sebesar 0,39%, untuk sifilis 1,7% dan untuk Hepatitis B 2,5%. Resiko penularan dari ibu ke bayi untuk HIV/AIDS 25-45%, sedangkan sifilis 60-80% dan Hepatitis B sekitar 90%. Sesuai dengan surat edaran Menteri Kesehatan Nomor HK.02.01/Menkes/37/2017 kepada IBI mengenai dukungan Pelaksanaan Eliminasi Penularan HIV, Sifilis dan Hepatitis B dari Ibu ke Anak di Indonesia.Tujuan: peneliian ini bertujuan untuk mengetahui partisipasi bidan dalam implementasi program Triple Eliminasi HIV, Sifilis dan Hepatitis B dari Ibu ke Anak di Pulau Lombok.Metode:Survei analitik menggunakan rancangan penelitian cross sectional study.Hasil: hasil penelitian menunjukkan bahwa hubungan bermakna antara usia responden dengan partisipasi bidan dalam program triple eliminasi dilihat dari nilai p=0,02 dan nilai OR 2.31 yang dapat diartikan usia responden ≤30 tahun berpeluang 2.3 kali untuk mempengaruhi partisipasi bidan dalam program triple eliminasi di Pulau Lombok.Simpulan : ada hubungan bermakna antara usia responden dengan partisipasi bidan dalam program triple eliminasiKatakunci: Partisipasi bidan, program triple eliminasi HIV, Sifilis dan Hepatitis B. Participation of Midwives in the Implementation of the Triple Elimination Program of HIV, Syphilis and Hepatitis B from Mother to Child on the Island of Lombok Background: The number of HIV infections in NTB Province from the time it was first discovered until March 2017 was 1,279, while the number of AIDS infections from 1987 to March 2017 was 704 people. The most risk factors for transmission are heterosexual (68%), IDU (11%), followed by homosexuals (4%), and perinatal transmission (3%). The prevalence in pregnant women for HIV is 0.39%, for syphilis 1.7%, and for Hepatitis B 2.5%. The risk of transmission from mother to baby for HIV/AIDS is 25-45%, while syphilis is 60-80% and Hepatitis B is around 90%. In accordance with the circular letter of the Minister of Health Number HK.02.01/Menkes/37/2017 to IBI regarding the support for the Implementation of Elimination of Transmission of HIV, Syphilis, and Hepatitis B from Mother to Child in Indonesia.Objective: This study aims to determine the participation of midwives in the implementation of the Triple Elimination program for HIV, Syphilis, and Hepatitis B from Mother to Child on the island of Lombok.Methods: Analytical survey using a cross-sectional study design.Results: The results showed that there was a significant relationship between the age of the respondent and the participation of midwives in the triple elimination program seen from the p-value = 0.02 and the OR value of 2.31 which means that the age of the respondent 30 years has a 2.3 times chance to influence the participation of midwives in the triple elimination program in Lombok island.Conclusion: there is a significant relationship between the age of the respondents and the participation of midwives in the triple elimination programKeywords: Participation of midwives, triple elimination program for HIV, syphilis, and hepatitis B.